Engineered Cu-PEN Composites at the Nanoscale: Preparation and Characterisation - Pryjmaková, Jana; Hryhoruk, Mariia; Veselý, Martin; Slepička, Petr; Švorčík, Václav; Siegel, Jakub (Nanomaterials (Basel, Switzerland), 2022)
As polymeric materials are already used in many industries, the range of their applications is constantly expanding. Therefore, their preparation procedures and the resulting properties require considerable attention. In this work, we designed the surface of polyethylene naphthalate (PEN) introducing copper nanowires. The surface of PEN was transformed into coherent ripple patterns by treatment with a KrF excimer laser. Then, Cu deposition onto nanostructured surfaces by a vacuum evaporation technique was accomplished, giving rise to nanowires. The morphology of the prepared structures was investigated by atomic force microscopy and scanning electron microscopy. Energy dispersive spectroscopy and X-ray photoelectron spectroscopy revealed the distribution of Cu in the nanowires and their gradual oxidation. The optical properties of the Cu nanowires were measured by UV-Vis spectroscopy. The sessile drop method revealed the hydrophobic character of the Cu/PEN surface, which is important for further studies of biological responses. Our study suggests that a combination of laser surface texturing and vacuum evaporation can be an effective and simple method for the preparation of a Cu/polymer nanocomposite with potential exploitation in bioapplications; however, it should be borne in mind that significant post-deposition oxidation of the Cu nanowire occurs, which may open up new strategies for further biological applications.
Keywords: periodic structures; nanostructured polymer; nanowires; nanocomposites; laser treatment